R for data science : import, tidy, transform, visualize, and model data - Wickham, Hadley; Grolemund, Garrett (Mumbai Shroff Publication, 2018)
"This book introduces you to R, RStudio, and the tidyverse, a collection of R packages designed to work together to make data science fast, fluent, and fun. Suitable for readers with no previous programming experience"--
Part I. Explore. Data visualization with ggplot2 -- Workflow: basics -- Data transformation with dplyr -- Workflow: scripts -- Exploratory data analysis -- Workflow: projects -- Part II. Wrangle. Tibbles with tibble -- Data import with readr --Tidy data with tidyr -- Relational data with dplyr -- Strings with stringr -- Factors with forcats -- Dates and times with lubridate -- Part III. Program. Pipes with magrittr -- Functions -- Vectors -- Iteration with purrr -- Part IV. Model. Model basics with modelr -- Model building -- Many models with purrr and broom -- Part V. Communicate. R Markdown -- Graphics for communication with ggplot2 -- R Markdown formats -- R Markdown workflow.
Includes bibliographical references and index.
Keywords: R (Computer program language); Data mining -- Computer programs; Information visualization -- Computer programs; Big data; Databases; Big data; Databases; Electronic data processing; R (Computer program language); Statistics